Legal Protection For Taxpayers In The Tax Examination Process - Moh Saleh; Handriono (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2021)
Tax auditing is something that is avoided by many taxpayers. However, due to one reason or another, the Taxpayer cannot avoid the Tax Audit. Therefore, the taxpayer should understand the process of a tax audit. The purpose of this research is to provide an overview of the things that need to be considered by taxpayers in facing the examination through a review of the Minister of Finance Regulation Number 184 / PMK.03 / 2015 concerning Amendments to PMK Number 17 / PMK.03 / 2013 concerning Procedures Examination. Through this study, it is hoped that it can help the taxpayers in understanding the tax audit process so that they can avoid things that harm the taxpayers. For the Directorate General of Taxes, the review is expected to be an input to improve existing laws and regulations related to tax audits in order to provide legal protection to taxpayers.